Jak uczyć innych i się zareklamować. AuthorTube – charakterystyka i kontrowersje - Strzelczyk, Agata (Studia Edukacyjne, 2025)
The aim of this article is to present the phenomenon of AuthorTube – YouTube channels offering writing advice, run by published or aspiring writers. Several of the most popular channels are presented, along with profiles of their hosts, such as Jenna Moreci, Meg LaTorre, Abbie Emmons, Alexa Donne, and Shaelin Bishop. The general nature of the advice they give is discussed, as well as controversies that have arisen within the community.